2018
DOI: 10.1002/cncy.21976
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid FNA biopsies comprised of abundant, mature squamous cells can be reported as benign: A cytologic study of 18 patients with clinical correlation

Abstract: The findings of the current study suggest that thyroid FNA specimens comprised almost exclusively of mature squamous cells can be reported as benign. Cancer Cytopathol 2018;126:336-41. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…TBSRTC is constantly evolving, as evidenced by the several modifications introduced in the second edition of TBSRTC 8 . Future revisions may consider amending the adequacy criteria to include squamous‐derived lesions 9,10 . Although rare, thyroid‐related lesions comprising squamous cells do exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TBSRTC is constantly evolving, as evidenced by the several modifications introduced in the second edition of TBSRTC 8 . Future revisions may consider amending the adequacy criteria to include squamous‐derived lesions 9,10 . Although rare, thyroid‐related lesions comprising squamous cells do exist.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, thyroid‐related lesions comprising squamous cells do exist. Intrathyroidal sources of benign squamous cells include cysts derived from developmental rests or remnants, as well as dermoid or epidermoid cysts 9,10 . Some authors have suggested that including these lesions with benign squamous cells into the Bethesda II category, even in the absence of thyroid follicular cells or colloid, would be reasonable 8–10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyst-lining cells are follicular cells that have undergone reactive changes including spindle- or elongated-shaped morphology, large round to oval nuclei with distinct nucleoli, fine chromatin, smooth nuclear contour, distinct cytoplasmic borders, and occasional exaggerated unipolar/bipolar cytoplasmic processes [3, 4]. Rarely, aspirates from the FNA may exclusively consist of benign-appearing, mature squamous cells [5]. It is worth noting that about 10–15% of thyroid nodules represent malignancy [6].…”
Section: Anterior Neckmentioning
confidence: 99%
“…The presence of ciliated cells, lymphocytes, squamous, colloid, and keratin are useful for the differential diagnosis. [50][51][52][53][54][55][56][57] The presence of a water-clear fluid mostly suggests parathyroid cysts, although a yellowish to brown cystic material is seen in thyroid cysts/pseudocysts. To note, occasionally PTC can be diagnosed in thyroglossal duct cysts.…”
Section: Other Cystic Lesionsmentioning
confidence: 99%